Relationship of surgeon experience and outcomes of surgery for degenerative mitral valve disease. Issue 8 (24th April 2021) - Yousef, Sameh; Singh, Saket; Mullan, Clancy W.; Dey, Pranammya; Mori, Makoto; Brooks, Cornell; Bin Mahmood, Syed Usman; Hashim, Sabet; Vallabhajosyula, Prashanth; Geirsson, Arnar
Abstract: Objective: To assess the impact of surgeon experience on the outcomes of degenerative mitral valve disease. Methods: We reviewed all patients who had surgery for degenerative mitral valve disease between 2011 and 2016. Experienced surgeon was defined as performing ≥ 25 mitral valve operations/year. Patient characteristics and outcomes were compared. Competing risk analysis was performed to identify factors associated with mitral regurgitation (MR) recurrence. Survival analysis for mortality was done using Kaplan Meier curve and Cox proportional hazard method. Results: There were 575 patients treated by 9 surgeons for severe MR caused by degenerative mitral valve disease between 2011 and 2016. Three experienced surgeons performed 77.2% of the operations. Patients treated by less experienced surgeons had worse comorbidity profile and were more likely to have an urgent or emergent operation ( p  = .001). Experienced surgeons were more likely to attempt repair ( p  = .024), to succeed in repair (94.7% vs. 87%; p  = .001), had shorter cross‐clamp times ( p  = .001), and achieved higher repair rate (81.3% vs. 69.7%; p  = .005). Experienced surgeons were more likely to use neochordae ( p  = .001) and less likely to use chordae transfer ( p  = .001). Surgeon experience was not associated with recurrence of moderate or higher degree of MR after repair but was an independent risk factor for mortality (HR = 2.64; p  = .002). Conclusions: Techniques of degenerative mitral valve surgery differ with surgeon experience, with higher rates of repair and better outcomes associated with more experienced surgeons.